Real-time correction by optical tracking with integrated geometric distortion correction for reducing motion artifacts in functional MRI. - Rotenberg, D; Chiew, M; Ranieri, S; Tam, F; Chopra, R; Graham, S (2013)
Head motion artifacts are a major problem in functional MRI that limit its use in neuroscience research and clinical settings. Real-time scan-plane correction by optical tracking has been shown to correct slice misalignment and nonlinear spin-history artifacts; however, residual artifacts due to dynamic magnetic field nonuniformity may remain in the data. A recently developed correction technique, Phase Labeling for Additional Coordinate Encoding, can correct for absolute geometric distortion using only the complex image data from two echo planar images with slightly shifted k-space trajectories. An approach is presented that integrates Phase Labeling for Additional Coordinate Encoding into a real-time scan-plane update system by optical tracking, applied to a tissue-equivalent phantom undergoing complex motion and an functional MRI finger tapping experiment with overt head motion to induce dynamic field nonuniformity. Experiments suggest that such integrated volume-by-volume corrections are very effective at artifact suppression, with potential to expand functional MRI applications.